ANALISIS TINGKAT KERAWANAN BENCANA BANJIR DI KOTA MAKASSAR DENGAN PEMANFAATAN GOOGLE EARTH ENGINE - Rayhan, Ahmad; Arfandi, Arfandi (Indonesian Journal of Applied Geography, 2025)
Flooding is one of the natural disasters that often occurs in many cities around the world, including in Makassar City, Indonesia. Flooding can be caused by various factors, such as high rainfall, poor drainage systems, and uncontrolled land use change. The impact of flooding can be very detrimental, both in terms of economic and social, including property losses. this research was conducted using a quantitative descriptive method which aims to describe the results of observations, proving the results of the analysis of the level of flood vulnerability by utilizing the Goole earth engine. Flood-prone areas are areas that from a physical and climatological point of view have the possibility of flood disasters within a certain period of time and have the potential to cause natural damage. Areas that have soil with poor water absorption, or rainfall that exceeds the soil's ability to absorb water. When heavy rains occur, there will be sudden flooding caused by the filling of dry drains with water. The zoning of the level of flood vulnerability in Makassar City is divided into 4, namely very vulnerable, vulnerable, less vulnerable, and not vulnerable. In general, Makassar City is included in the flood-prone class with physical characteristics, namely being in an area with a flat topography of 0-71 meters above sea level, rainfall amount of 2000 - 3000 mm / year, with a vegetation density of 0 to 5 meters, and a fairly low infiltration rate.